The image of a doctor in a doctor-patient relationship in the Internet era - Wiertlewska, Janina (Scripta Neophilologica Posnaniensia, 2019)
The following paper deals with the issues of doctor’s image in the doctor-patient relationship in the Internet era and the influence of Internet on patient’s compliance. Both positive and negative standpoints have been discussed briefly, followed by a description of a research model proposed by Laugesen, Hassanein and Yufei (2015) applicable for this type of study. The study examines the impact of patients’ use of Internet health information on various elements of patient-doctor relation (including compliance) through a theoretical model based on principal-agent theory as well as the information asymmetry perspective. A pilot survey and interview study performed on one Polish doctor and a group of his patients, a specialist in Family Medicine has been described. The study carried out by three coworkers: Laugesen, Hassanein and Yufei (2015) revealed that patient-doctor concordance and perceived information asymmetry have relevant effects on patient’s compliance while patient-doctor concordance reveals a stronger relationship. The final conclusions were such that only doctor’s quality had a significant influence on the information asymmetry; the Internet health information gathered by a patient had no impact on perceived information asymmetry; the pilot study performed on the Polish physician confirms the theses presented in this paper but further investigations concerning the formerly discussed issues should be done.